Determination of thallium in environmental samples by surfactant assisted dispersive liquid-liquid microextraction combined with first order derivative spectrophotometry - George, Louis; Varghese, Anitha; Nizam, Aatika (European Journal of Chemistry, 2015)
A surfactant assisted dispersive liquid-liquid microextraction (SA-DLLME) combined with derivative spectrophotometric method has been proposed for the determination of thallium(III) using a chelating agent diacetylmonoxime-p-hydroxybenzoylhydrazone. Disperser solvent was substituted by surfactant, which made the emulsification more effective and extraction, quite environment friendly. Carbon tetrachloride was employed as the extractant. The developed SA-DLLME technique was coupled with first order derivative spectrophotometric method to improve the analytical performance. Optimum conditions relevant to SA-DLLME and instrumental parameters were studied in detail. The enrichment factor of the method was found to be 23. The limit of detection and quantitation limit of first order derivative spectrophotometric method were found to be 0.22 and 0.67 µg/L, respectively. The relative standard deviation (RSD) for five replicates of 50.0 µg/L of thallium(III) was found to be 1.12%. The applicability of the method was evaluated by the trace level determination of thallium in different environmental samples.